Cesarean Section in the Second Delivery to Prevent Anal Incontinence After Asymptomatic Obstetric Anal Sphincter Injury: The EPIC Multicenter Randomized Trial. Issue 4 (22nd December 2021) - Abramowitz, L.; Mandelbrot, L.; Bourgeois Moine, A.; Tohic, A.L.; Carne Carnavalet, C.; Poujade, O.; Roy, C.; Tubach, F.
Abstract : ( BJOG . 2021;128:685–693. doi: 10.1111/1471-0528.16452) Anal incontinence negatively impacts the quality of life and sexual health of 14.8% of women in the United States. Third-degree and fourth-degree obstetric anal sphincter injuries, reported in 2% to 12% of vaginal deliveries (VD), contribute. Between 38% and 53% of obstetric anal sphincter lesions are associated with long-term anal incontinence. Up to 27% of women experience occult anal sphincter lesions following their first VD, and 9% of women with undiagnosed anal sphincter lesions experience anal incontinence. Instrumental delivery increases risk of anal incontinence with sphincter lesions occurring in 63% to 82% of forceps deliveries; 23% of these parturients experiencing anal incontinence. When anal sphincter injuries occur during the first VD, cesarean delivery (CD) is an option for future births. Although CD may have beneficial maternal outcomes, there are risks to both mother and neonate and no clear evidence to aid decision making. The aim of this study was to identify whether CD for the second delivery could prevent anal incontinence in women with a history of asymptomatic obstetric anal sphincter injuries.